2012
DOI: 10.1111/j.1600-0838.2010.01119.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing patellar tendon loading during the landing phases of a stop‐jump task

Abstract: Excessive extensor mechanism loading from repeated landing has been associated with overuse knee injuries, especially patellar tendinopathy. In order to reduce these loads, it is important to establish which landing task places the highest load on the patellar tendon. It was hypothesized that the horizontal landing would create higher patellar tendon force (F(PT)) compared with the vertical landing. Sixteen male athletes with healthy patellar tendons performed five successful trials of a stop-jump task, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 36 publications
6
31
0
2
Order By: Relevance
“…With respect to the Cardanic axes of the local joint coordinate system, intersegmental joint angles were expressed for knee and hip joint angles as flexion-extension, adductionabduction, and intemal-extemal rotation; and trunk angles as extension-flexion, right-left lateral fiexion, and left-right rotation. Using the 18-Hz filtered kinetic data, the horizontal landing phase was defined from IC when the vertical ground reaction force exceeded 10 N to the first local minimum, to peak knee joint flexion angle (Kneemax)-For each trial, the maximum vertical jump height (11), knee and hip joints, and trunk segment kinematics at IC and at the time of the KneeMax were calculated.…”
Section: Pta Dimensionsmentioning
confidence: 99%
“…With respect to the Cardanic axes of the local joint coordinate system, intersegmental joint angles were expressed for knee and hip joint angles as flexion-extension, adductionabduction, and intemal-extemal rotation; and trunk angles as extension-flexion, right-left lateral fiexion, and left-right rotation. Using the 18-Hz filtered kinetic data, the horizontal landing phase was defined from IC when the vertical ground reaction force exceeded 10 N to the first local minimum, to peak knee joint flexion angle (Kneemax)-For each trial, the maximum vertical jump height (11), knee and hip joints, and trunk segment kinematics at IC and at the time of the KneeMax were calculated.…”
Section: Pta Dimensionsmentioning
confidence: 99%
“…This study reported good to excellent reliability within and between sessions when assessed using coefficient of multiple correlation (Kadaba et al, 1989) and interclass correlation coefficients. However, stop jumps (SJ) are also commonly used in the literature to assess jumping performance both within a single session (Chappell et al, 2002;Edwards et al, 2010;Myers and Hawkins, 2010) and longitudinally (Chappell and Limpisvasti, 2008;Herman et al, 2009Herman et al, , 2008Oñ ate et al, 2005). To fully interpret the results of single session studies, it is important to understand the trial to trial reliability of the task within a session.…”
Section: Introductionmentioning
confidence: 99%
“…49 Higher patellar tendon forces are reported in the horizontal landing phase of a stop land/jump sequence, with peak patellar tendon forces of 6.6  1.6 body weight and loading rates up to 93  23 body weight per second. 28 This provides an understanding that the major change through these activities is rate of loading of the tendon, which should be progressed gradually through relevant energy-storage activities for the individual athlete.…”
mentioning
confidence: 99%